Ética jurídica y filosofía política. Homenaje Eusebio Fernández García - Delgado Rojas, Jesús Ignacio (EUNOMÍA. Revista en Cultura de la Legalidad, 2024)
The tribute to Professor Eusebio Fernández García, held on July 3, 2024 at Universidad Carlos III de Madrid, commemorated his career after almost 50 years of teaching in Philosophy of Law and Political Philosophy. Recognized for his academic work, Fernández has directed multiple doctoral theses and published 10 monographs, more than 150 articles and co-edited 7 books. At the event, colleagues and disciples discussed his influence on topics related to the philosophy of law, political philosophy, legal ethics and the theory of human rights. The event culminated with the presentation and re-publication of his work Teoría de la Justicia y Derechos Humanos, reaffirming his academic and philosophical legacy.
Keywords: Eusebio Fernández; tribute; philosophy of law; ethics; political philosophy